Spinel Zn3V3O8 nanosheets via a one-step hydrothermal synthesis with peroxidase-like activity for high sensitivity glucose colorimetric detection in synthetic perspiration. Issue 23 (25th May 2021) - Yang, Guizeng; Lu, Yi; Li, Yi; Ying, Meihui; Pan, Haibo; Qi, Jiayuan; Du, Min
Abstract : Hydrogen peroxide reacts with V 4+ on (011) exposed facet of 2D Zn3 V3 O8 nanosheets to produce a hydroxyl radical via a Fenton-like reaction and its peroxidase-like activity is applied to glucose colorimetric detection. Abstract : Due to their specific spinel structure, ternary oxides with multi-catalytic sites on a highly active exposed surface are recommended as alternative bio-catalysts. Spinel zinc vanadate with two-dimensional nanosheets (Zn3 V3 O8 NSs) was synthesised using a one-step hydrothermal route with CTAB and glycine as a bi-surfactant, where each NS has a thin thickness (25 nm) and wide cross section (2 μm). As a key parameter for peroxidase-like activity, the Michaelis–Menten constant ( K m ) for Zn3 V3 O8 NSs was calculated to be 0.271 mM with TMB and 1.317 mM with H2 O2 at optimum conditions, indicating a higher affinity for the exposed (011) facet towards horseradish peroxidases. This affinity is related to the geometric matching between V 4+ active sites and the terminal amino groups of TMB. The V 4+ ions on the (011) facet act as dangling bonds and readily react with H2 O2 in a Fenton-like reaction. The peroxidase-like activity for Zn3 V3 O8 NSs is verified by the formation of [V(IV)–OO˙] by the ˙O2 − and V 5+ near V 4+ sites, but oxidase activity for Zn3 V3 O8 NSs. Based on the peroxidase-like activity, Zn3 V3 O8 NSs were used as a colorimetric glucose sensor with a wide linear range from 0.01 to 0.5 mM and a detection limit (LOD = 3 σ / S ) of 2.81 × 10 −7 M. The colorimetric sensor also exhibited high accuracy and selectivity in synthetic perspiration samples.